The Role of Speech and Language Therapists (SLTs) in International Stroke Teams: A Systematic Review - Charalambous, Marina; Pierce, John E.; Pastou, Georgia; Kola, Erasmia; Savitz, Sean I. (My University, 2025)
Current published guidelines suggest that speech and language therapists (SLTs) should be part of stroke teams, but their involvement and roles according to country income are unknown.
Keywords: systematic review; countries; multidisciplinary team; rehabilitation; speech and language therapists; stroke